SQL - Fehily, Chris (Berkeley, CA : Peachpit Press, 2008)
SQL is a standard interactive and programming language for querying and modifying data and managing databases. This task-based tutorial and reference guide takes the mystery out learning and applying SQL. After going over the relational database model and SQL syntax in the first few chapters, veteran author Chris Fehily immediately launches into the tasks that will get readers comfortable with SQL. In addition to covering all the SQL basics, this thoroughly updated reference contains a wealth of in-depth SQL knowledge and serves as an excellent reference for more experienced users.
Machine generated contents note: Ch. 1 DBMS Specifics -- Ch. 2 Relational Model -- Ch. 3 SQL Basics -- Ch. 4 Retrieving Data from a Table -- Ch. 5 Operators and Functions -- Ch. 6 Summarizing and Grouping Data -- Ch. 7 Joins -- Ch. 8 Subqueries -- Ch. 9 Set Operations -- Ch. 10 Inserting, Updating, and Deleting Rows -- Ch. 11 Creating, Altering, and Dropping Tables -- Ch. 12 Indexes -- Ch. 13 Views -- Ch. 14 Transactions -- Ch. 15 SQL Tricks.
Includes index.
Keywords: SQL (COMPUTER PROGRAM LANGUAGE)